2014
DOI: 10.1177/0272431614523133
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Media Multitasking and Executive Function in Early Adolescents

Abstract: The increasing prevalence of media multitasking among adolescents is concerning because it may be negatively related to goal-directed behavior. This study investigated the relationship between media multitasking and executive function in 523 early adolescents (aged 11-15; 48% girls). The three central components of executive functions (i.e., working memory, shifting, and inhibition) were measured using self-reports and standardized performance-based tasks (Digit Span, Eriksen Flankers task, Dots–Triangles task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
169
10
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(220 citation statements)
references
References 39 publications
27
169
10
14
Order By: Relevance
“…The relationship seen here between media multitasking and working memory stands in contrast to the results of Baumgartner et al (2014), who found no relationship between MMI and working memory. This difference may reflect the extent to which different working memory measures indexed the executive aspects of working memory.…”
Section: Executive Functionscontrasting
confidence: 99%
See 1 more Smart Citation
“…The relationship seen here between media multitasking and working memory stands in contrast to the results of Baumgartner et al (2014), who found no relationship between MMI and working memory. This difference may reflect the extent to which different working memory measures indexed the executive aspects of working memory.…”
Section: Executive Functionscontrasting
confidence: 99%
“…Greater media multitasking was associated with self-reports of worse executive function in a large sample of adolescents (Baumgartner, Weeda, van der Heijden, & Huizinga, 2014). Contrary to the self-reports, when assessed experimentally, Baumgartner et al found evidence for an association between heavier media multitasking and better inhibitory control (i.e., more easily ignoring distractors in an Eriksen flanker task), but no relationships with task switching or working memory performance.…”
Section: Abstract Media Multitasking Adolescents Standardized Tesmentioning
confidence: 91%
“…The literature is scarce and presents inconsistent results. For example, some findings point to the detrimental effects of frequent multitasking on the performance in laboratory tests of executive function (8), and a negative relationship between multitasking and self-reported cognitive functioning (24). Conversely, other studies failed to support the findings that heavy media multitasking is related to poor cognitive performance (25), or even provided evidence for a positive relationship between media multitasking and the ability to integrate information from multiple sensory systems (26).…”
Section: Discussionmentioning
confidence: 99%
“…Baumgartner, Weeda, van der Heijden, & Huizinga, 2014;Minear, Brasher, McCurdy, Lewis, & Younggren, 2013;Ralph, Thomson, Seli, Carriere, & Smilek, 2014;Wang & Tchernev, 2012). Understandably, a significant area of focus in recent research is the safety implications of using a cellphone while driving (e.g.…”
mentioning
confidence: 99%